Investigation of Charge Transfer Complex Formation Between Fe(III) and 2,6-Dihydroxy Benzoic Acid and its Applications for Spectrophotometric Determination of Iron in Aqueous Media - Mohammad Saeid Hosseini; Sara Madarshahian (E-Journal of Chemistry)
On the basis of affinity of Fe(III) ions toward functional groups of 2,6-dihydroxy benzoic acid (2,6-DHB), a charge transfer complex (CT) is formed between Fe(III) ion and 2,6-DHB in acidic media. The stoichiometry and stability constant of the complex was determined using both mole ratio and Job’s methods. The stability constant of 1:1 complex formed in acidic media is 2.55±0.14×105 (mole ratio) or 2.70±0.12×105 (Job), in which the quantities are in agreement with together. This method was used for spectrophotometric determination of Fe(III) in aqueous media. The dynamic range and detection limit (DL) were 1.2×10-5 to 3.6×10-4 M and 1.5×10-6 M, respectively. The relative standard deviation (RSD) was found to be 0.76% in the replicate treatments (n=7) with 1.6×10-4 M Fe(III). The practical applicability of the method was confirmed using a synthetic certificated reference material (CRM) and spiked natural water samples.